Means of livelihood, clean environment to women empowerment: The multi-faceted role of donkeys - Ravichandran, Thanammal; Perumal, Ramesh K.; Kennady, Vijayalakshmy; Raw, Z.; Cooke, F.; Baltenweck, Isabelle; Rahman, Habibar (MDPI, 2023)
Despite the substantial contribution donkeys make to the livelihood of the world’s poorest populations, the existence of donkeys has received little notice worldwide. This article reviews the value of donkeys in a variety of sectors, including agriculture, construction industry, and mining, as well as their role in empowering women and achieving sustainable development goals. However, donkeys and mules are not given enough credit or attention in terms of developing strategies regarding their role in reducing poverty. There is a dearth of information and statistics on their impact across industries, the factors contributing to the donkey population dropping, the socioeconomic status of the dependent communities, and related animal and human welfare issues.